2004
DOI: 10.1177/0273475303262354
|View full text |Cite
|
Sign up to set email alerts
|

Academic Dishonesty: A Cross-Cultural Comparison of U.S. and Chinese Marketing Students

Abstract: Chinese as well as American business colleges are attempting to improve morality of their students due to recent scandals in both countries. This study investigates several beliefs and values, opportunism, and certain demographic variables that might contribute to the academic dishonesty of American and Chinese marketing students. The findings suggest that American marketing students who are young, tolerant, detached, relativistic, less religious, opportunistic, and negative tend to believe that academic disho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 43 publications
0
65
0
1
Order By: Relevance
“…However, corruption indices measure perceptions and not actual behaviors. Further, variations across countries in academic dishonesty (Rawwas et al, 2004) and tax evasion (Alm et al, 1995;Cummings et al, 2009) reinforce the impression that cheating is both abundant and diverse around the world. In the same line, recent research in behavioral and experimental economics has shown that a large fraction of individuals are prone to cheating (Ariely, 2012;Gneezy, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…However, corruption indices measure perceptions and not actual behaviors. Further, variations across countries in academic dishonesty (Rawwas et al, 2004) and tax evasion (Alm et al, 1995;Cummings et al, 2009) reinforce the impression that cheating is both abundant and diverse around the world. In the same line, recent research in behavioral and experimental economics has shown that a large fraction of individuals are prone to cheating (Ariely, 2012;Gneezy, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…[3][4][5][6] Given the numerous incentives, cheating occurs across disciplines and beyond college into diverse professions. [7][8][9][10][11][12] Several studies suggest that cheating is prevalent and steadily increasing in health disciplines that place significant emphasis on high ethical standards, integrity, and professionalism, such as medicine, dentistry, pharmacy, and nursing. 7,[12][13][14][15][16] Baldwin and colleagues reported that 39% of medical student respondents witnessed some type of cheating among classmates during the first 2 years of their medical education, 67% had heard about cheating, and 5% admitted cheating during medical school.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of these concerns, researchers emphasized the need to conduct studies that investigate students' ethical decisions making (McCabe& Pavela, 2004;Pincus & Schmelkin, 2003;Rawwas, Al-Khatib, & Vitell, 2004). Additionally, organizational behavior literature provides support that employees' code of conduct awareness and their ethical decision making are potential contributing constructs to their use of IS (Cronan et al, 2005;Kreie & Cronan, 1998).…”
Section: Ethical Decision Making In E-learningmentioning
confidence: 99%